2021
DOI: 10.1007/s10694-021-01098-x
|View full text |Cite
|
Sign up to set email alerts
|

Prototyping and Validating a Non-immersive Virtual Reality Serious Game for Healthcare Fire Safety Training

Abstract: In a healthcare context, the success of a fire safety procedure in a real-life emergency mainly depends on staff decisions and actions. One of the factors influencing staff decision-making is their training. In most healthcare facilities, safety educators use slide-based lectures as a training tool. Virtual Reality (VR) is gaining fire safety community attention for being an interesting training tool. However, few studies have assessed the effectiveness of VR-based fire safety training simulators compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 34 publications
5
25
0
Order By: Relevance
“…This possibility, which was already applied to the former project 3D-IMP-ACT, could be a further improvement of the present study, particularly for those records, such as diagnostic reports on construction materials/elements or 3D models, that might be analysed and compared across different case studies, through spatial and parametric interrogation of the geographic information system. Finally, as the future development of the proposed workflow and application, the validation should be supported by the results of feedback questionnaires, structured to provide a metric for usability, effectiveness, motion sickness, sense of presence and realism of the virtual environment (Mastrolembo Ventura et al, 2020), as well as retention and self-efficacy for training purposes under emergency (Chittaro & Sioni, 2015;Falconer et al, 2020;Lovreglio et al, 2018;Rahouti et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility, which was already applied to the former project 3D-IMP-ACT, could be a further improvement of the present study, particularly for those records, such as diagnostic reports on construction materials/elements or 3D models, that might be analysed and compared across different case studies, through spatial and parametric interrogation of the geographic information system. Finally, as the future development of the proposed workflow and application, the validation should be supported by the results of feedback questionnaires, structured to provide a metric for usability, effectiveness, motion sickness, sense of presence and realism of the virtual environment (Mastrolembo Ventura et al, 2020), as well as retention and self-efficacy for training purposes under emergency (Chittaro & Sioni, 2015;Falconer et al, 2020;Lovreglio et al, 2018;Rahouti et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Perceptual input is an area that appears in HCI which suggests that the Development of a Perceptual User Interface (PUI) is a part that encourages total Immersion so that Serious Game users using cellular can form an immersive social networking environment because there are various kinds of input devices, software platforms, interaction possibilities, and various ways to combine all of the above elements in achieving the PUI concept (Mentzelopoulos et al, 2015). VR-based fire safety training for healthcare staff at Vincent Van Gogh Hospital (VVG) in Belgium demonstrates that VR SG is more effective than slide-based lectures in terms of knowledge acquisition and retention and increasing self-efficacy in the short and long term than college; slide-based (Rahouti et al, 2021).…”
Section: Total Immersionmentioning
confidence: 99%
“…Although the fire‐safety knowledge of both groups increased significantly after training, the increase in knowledge in the virtual reality group was more than that of the standard training group. Most of the virtual reality group indicated that they had a positive experience with it and believed it was effective for improving their knowledge, although they suggested that using immersive rather than non‐immersive virtual reality would help them feel more absorbed in the scenario 4 …”
Section: Trainingmentioning
confidence: 99%